A new perspective on technology‐driven creativity enhancement in the Fourth Industrial Revolution. (3rd November 2021) - Pedota, Mattia; Piscitello, Lucia
Abstract : Technology is generally assumed to complement workers performing creative tasks by enhancing their ability to gather, store, share and transform knowledge. We advance an alternative view by conceptualizing how technology complements workers also by extending the domain, namely the set of symbolic and material elements underlying a given creative task. We elucidate the ways in which a domain extension complements workers' individual components of creativity, namely, domain‐relevant skills, creativity‐relevant processes and task motivation. Furthermore, we underline the importance of renewing heuristics to reap the creativity‐enhancing potential of the domain extension, as well as the role of the organizational context in this regard. Finally, we provide an illustrative example of our framework, referring to the adoption of additive manufacturing in Luxottica.